Conversion of Provider EMR Training from Instructor-Led Training to eLearning at an Academic Medical Center - Sharp, Karen; Williams, Michele; Aldrich, Alison; Bogacz, Adrienne; Denier, Sighle; McAlearney, Ann S. (Applied Clinical Informatics, 2017)
This case study overviews the conversion of provider training of the electronic medical record (EMR) from an instructor-led training (ILT) program to eLearning at an Academic Medical Center (AMC). This conversion provided us with both a useful training tool and the opportunity to maximize efficiency within both our training and optimization team and organization. eLearning Development Principles were created and served as a guide to assist us with designing an eLearning curriculum using a five step process. The result was a new training approach that allowed learners to complete training at their own pace, and even test out of sections based on demonstrated competency. The information we have leads us to believe that a substantial return on our investment can be obtained from the conversion with positive impacts that have served as the foundation for the future of end user EMR training at our AMC.Citation: Sharp K, Williams M, Aldrich A, Bogacz A, Denier S, McAlearney AS. Conversion of Provider EMR Training from Instructor Led Training to eLearning at an Academic Medical Center. Appl Clin Inform 2017; 8: 754–762 https://doi.org/10.4338/ACI-2017-03-CR-0040
Keywords: Electronic health records and systems; Knowledge translation; Internet and the Web technology; Strategies for health IT training; Employee orientation program